Comorbidity of depressive disorders in adolescents and young adults with self-destructive behaviour and eating disorders - Pukhovskyi Богдан; Pyliagina Галина (Psychosomatic Medicine and General Practice, 2025)
Background: Depressive Disorders (DD) are often complicated by comorbid behavioral disturbances, especially in adolescence and young adulthood. Complex cases of DD comorbid with Self-Destructive Behavior (SDB), including Eating Disorders (ED) as a severe equivalent form, represent a pressing issue in modern psychiatry. Objective: To study the clinical features of DD in adolescence and youth and their comorbidity with ED and SDB according to gender. Materials and Methods: The study examined 130 outpatients (94 females, 36 males) aged 14–19 years with DD (F92, F32-34) combined with ED (F50). Methods included a semi-structured clinical interview, the Beck Depression Inventory (BDI ≥ 14 points), and the Purpose-in-Life Test (SJO). Results: 100% of the examined patients exhibited some manifestation of SDB. Adjustment Depressive Disorder (F43.2) significantly prevailed in young males (44.44%, p<0.05), indicating vulnerability to chronic stress. Non-suicidal self-cuts and excoriations significantly predominated in females (74.5%, p=0.000), primarily aiming to reduce anxiety and internal tension. Suicidal fantasies significantly predominated in young males (22.2%, p=0.029). The complex comorbidity of DD with SDB and ED significantly worsens the patients’ condition and exacerbates suicidal urges. Conclusion: The presence of SDB is a near-obligatory feature in youth suffering from DD. Significant gender differences exist in the manifestation of this comorbidity, necessitating a comprehensive and differentiated approach to diagnosis and treatment. Keywords: diagnostics of mental disorders, depressions, depression conduct disorder, eating disorders, binge-eating disorder, self-destructive behavior, comorbidity of mental disturbances, mental disorders in adolescence and young adult age, psychodiagnostic study